The development of individual counseling guidelines for assertive training techniques to improve student assertiveness in state senior high schools in Yogyakarta - Tiara Erganila; Budi Astuti; Le Ngoc Ai Nhung (Research and Social Study Institute, 2022)
This study aims to produce an individual counselling guide for assertive training techniques in State Senior High Schools in Yogyakarta. This research is research and development using the Borg & Gall development model, which was conducted through seven stages: preliminary research and data collection, planning, initial product development, early-stage trial, revision of early-stage trial, field trial, and field trial revision. Data collection methods used a questionnaire on the feasibility of assessing material experts, media experts, guidance and counselling teachers, and students' assertive behaviour scale. The data analysis technique used in this research is descriptive quantitative. This study resulted in (1) individual counselling guidelines, which consisted of an introduction, behavioristic approach, assertive nature, assertive training, implementation of assertive training techniques, conclusions, references, and attachments. (2) Assertive training technique guidebook can be categorized as “very good” with a final percentage value of 84.6%, 78% by material experts, and 88,3% by media experts. (3) The results of the field trial of three guidance and counselling teachers got a percentage value of 85.3%, which included the “very good” category, and the results of the main field trial of ten guidance and counselling teachers got a percentage value of 87.1% in “very good” category.